Algorithm-driven activity-directed expansion of a series of antibacterial quinazolinones. Issue 48 (30th November 2022) - Francis, Daniel; Farooque, Sannia; Meager, Archie; Derks, Didi; Leggott, Abbie; Warriner, Stuart; O'Neill, Alex J.; Nelson, Adam
Abstract : Algorithms were harnessed in the design of arrays of photoredox-catalysed microscale reactions whose crude products were screened for antibacterial activity. The approach enabled expansion of a series of antibacterial agents. Abstract : Activity-directed synthesis (ADS) is a structure-blind, function driven approach that can drive the discovery of bioactive small molecules. In ADS, arrays of reactions are designed and executed, and the crude product mixtures are then directly screened to identify reactions that yield bioactive products. The design of subsequent reaction arrays is then informed by the hit reactions that are discovered. In this study, algorithms for reaction array design were developed in which the reactions to be executed were selected from a large set of virtual reactions; the reactions were selected on the basis of similarity to reactions known to yield bioactive products. The algorithms were harnessed to design arrays of photoredox-catalysed alkylation reactions whose crude products were then screened for inhibition of growth of S. aureus ATCC29213. It was demonstrated that the approach enabled expansion of a series of antibacterial quinazolinones. It is envisaged that such algorithms could ultimately enable fully autonomous activity-directed molecular discovery.